Antistatic visual pipe material for cigarette filter rod conveying and method for producing the same

CN122917533APending Publication Date: 2026-10-16HUBEI JINTIANYE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611322950.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0011]有鉴于此,本发明提供了一种用于卷烟滤嘴棒输送的抗静电可视管道材料及其制备方法,以解决现有技术中管道材料不可视化、静电积聚、摩擦阻力大、食品安全性不足等技术问题

Benefits of technology

[0035]经由上述的技术方案可知,与现有技术相比,本发明取得的有益效果至少包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of high polymer composite materials, and discloses an antistatic visual pipeline material for conveying cigarette filter rods and a preparation method thereof. The antistatic visual pipeline material comprises the following components in parts by weight: 60-80 parts of a transparent polyamide matrix, 8-18 parts of a polyether ester amide permanent antistatic agent, 3-8 parts of a polyether block amide auxiliary antistatic agent, 0.5-2 parts of a quaternary ammonium salt surfactant, 2-5 parts of a maleic anhydride grafted polyolefin elastomer compatibilizer, 0.3-1.5 parts of an ultrahigh molecular weight polysiloxane lubricant, and 0.2-0.8 parts of a hindered phenol / phosphite composite antioxidant. The synergistic compounding of the polyether ester amide permanent antistatic agent, the polyether block amide auxiliary antistatic agent and the quaternary ammonium salt surfactant forms a ternary synergistic antistatic system, realizes full visual monitoring, stable static dissipation and low-friction high-efficiency conveying, and has significant industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials technology, and more specifically to an antistatic visible pipe material for conveying cigarette filter rods and its preparation method, particularly to a special pipe material that simultaneously possesses high light transmittance and visibility, long-lasting antistatic properties, and low friction and non-stick properties. Background Technology

[0002] In the cigarette production process, filter rods are transported at high speed to the cigarette-making unit through a pneumatic conveying system in a sealed pipeline. Currently, stainless steel or ordinary plastic pipes are commonly used in industry for filter rod transport, but the following technical problems exist:

[0003] (1) Lack of visibility: Traditional stainless steel pipes are opaque and cannot monitor the conveying status of filter rods in the pipeline in real time. When abnormal situations such as material blockage, filter rod damage, or flying material occur, it is difficult to detect and locate them in time, which affects production efficiency and product quality.

[0004] (2) Static charge accumulation: During high-speed pneumatic conveying, the filter rod continuously rubs against the pipe wall, generating static charge accumulation. The surface resistivity of traditional plastic pipes (such as PVC, ordinary PA, etc.) is as high as 10. 12 ~10 15 If the static electricity is too high (Ω / sq), it cannot be effectively dissipated, causing the filter rod to adhere to the tube wall and clog the pipeline. In severe cases, it may even lead to the risk of dust explosion.

[0005] (3) High frictional resistance: The friction coefficient of the inner wall of ordinary plastic pipes is high (usually >0.3), resulting in high resistance to filter rod transport, high energy consumption, and easy wear on the surface of filter rod.

[0006] (4) Food safety: Pipe materials must meet the safety standards for food contact materials to prevent the migration of harmful substances and contamination of the filter rod.

[0007] Transparent polyamides possess transparency, high strength, and high toughness, and are non-toxic and odorless, meeting FDA and EU standards for use in the food industry. With a light transmittance exceeding 90%, they enable full-process visual monitoring when used as the main material for cigarette filter delivery pipes. However, polyamides themselves lack sufficient antistatic properties, necessitating antistatic modification to inhibit surface static buildup and ensure product cleanliness and delivery stability.

[0008] CN122188391A discloses an antistatic and high wear-resistant PA66 composite material, but it uses conductive filler (aramid fiber / polypyridine composite) as the antistatic component, and the material is opaque, which cannot meet the application requirements for visualization.

[0009] Chinese invention patent application number 201611227099.4 discloses a wear-resistant and antistatic polyamide composite material and its preparation method. This patent uses modified graphene and carbon black as antistatic additives, and modified hexagonal boron nitride microflakes and silicon carbide capsules as wear-resistant agents. The wear-resistant and antistatic polyamide material is prepared by twin-screw co-extrusion. Although this material has advantages such as low wear and good antistatic properties, it is opaque and has very poor mechanical properties.

[0010] Therefore, how to provide a special pipe material that simultaneously achieves high light transmittance and visibility, long-lasting antistatic properties, low friction and non-stick properties, food-grade non-toxicity, and compatibility with high-speed pneumatic tobacco conveying is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0011] In view of this, the present invention provides an antistatic visible pipe material for conveying cigarette filter rods and its preparation method, so as to solve the technical problems of non-visualization, static electricity accumulation, high frictional resistance, and insufficient food safety in the prior art.

[0012] To achieve the above objectives, the present invention adopts the following technical solution:

[0013] One objective of this invention is to provide an antistatic visible conduit material for conveying cigarette filter rods, comprising the following components by weight:

[0014] The composition includes 60-80 parts of transparent polyamide matrix, 8-18 parts of polyether ester amide permanent antistatic agent, 3-8 parts of polyether block amide auxiliary antistatic agent, 0.5-2 parts of quaternary ammonium salt surfactant, 2-5 parts of maleic anhydride grafted polyolefin elastomer compatibilizer, 0.3-1.5 parts of ultra-high molecular weight polysiloxane lubricant, and 0.2-0.8 parts of hindered phenol / phosphite composite antioxidant.

[0015] The transparent polyamide matrix is ​​one or a combination of two of semi-aromatic transparent polyamide or long-chain transparent polyamide, with a light transmittance ≥88% under test conditions of 550nm wavelength and 3mm material thickness; the number average molecular weight of the polyether ester amide permanent antistatic agent is 8000-20000; and the number average molecular weight of the polyether block amide auxiliary antistatic agent is 5000-15000.

[0016] Preferably, the transparent polyamide matrix is ​​selected from at least one of PA12, PA612, PA1012, transparent copolyamide PA (MACM12), and transparent copolyamide PA (PACM12), with a number average molecular weight of 15,000 to 50,000 and a water content of ≤0.1wt%.

[0017] Preferably, the polyether ester amide permanent antistatic agent is a polyether ester amide block copolymer, wherein the content of polyether soft segments is 40-60 wt% and the content of polyamide hard segments is 40-60 wt%; the polyether soft segments are one or a combination of two of polyethylene glycol (PEG) or polytetrahydrofuran (PTMG), with a number average molecular weight of 1000-4000.

[0018] Polyether ester amide-based permanent antistatic agents contain both polyamide hard segments and polyether soft segments in their molecular chains. The polyamide hard segments exhibit good thermodynamic compatibility with the transparent PA matrix and can achieve molecular-level dispersion through intermolecular hydrogen bonding. The ether oxygen atoms in the polyether soft segments possess lone pairs of electrons, which can form hydrogen bonds with water molecules, creating a conductive water film on the material surface and constructing ion conduction channels. This component provides the primary antistatic function of the material, endowing it with permanent antistatic properties.

[0019] Preferably, the polyether block amide auxiliary antistatic agent is a PEBAX type polyether block amide with a Shore hardness of 60A to 72D and a melting point of 130 to 170°C.

[0020] PEBAX-type polyether block amides possess a unique microphase separation structure of hard and soft segments. Within a transparent PA matrix, they can form nanoscale hydrophilic microdomains, which, together with the soft segments of polyether ester amide permanent antistatic agents, form an interpenetrating network structure, further expanding the connectivity of conductive channels. Simultaneously, the flexible segments of this component improve the material's toughness and reduce the embrittlement effect caused by the addition of antistatic agents.

[0021] Preferably, the maleic anhydride-grafted polyolefin elastomer compatibilizer is one of POE-g-MAH or EPDM-g-MAH, with a maleic anhydride grafting rate of 0.5-2.0 wt% and a melt index of 1-10 g / 10 min (190°C, 2.16 kg).

[0022] Preferably, the ultra-high molecular weight polysiloxane lubricant has a molecular weight of 500,000 to 5,000,000 and a kinematic viscosity of 10,000 to 100,000 cSt (25°C).

[0023] Preferably, the quaternary ammonium salt surfactant is one of bis(octadecyl)dimethylammonium chloride or methylbis(2-hydroxyethyl)cocoylammonium chloride.

[0024] The quaternary ammonium salt cationic groups possess strong hydrophilicity, enabling rapid migration to the material surface to form a conductive layer and provide immediate antistatic effects. Simultaneously, the long carbon alkyl chains of the quaternary ammonium salt exhibit hydrophobic interactions with the PA matrix, slowing down the surface migration rate and prolonging the antistatic durability. This component, together with permanent and auxiliary antistatic agents, forms a dual "bulk-interface" antistatic mechanism.

[0025] Preferably, the hindered phenol / phosphite composite antioxidant is a compound of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl)phosphite, with a mass ratio of 1:1 to 2:1.

[0026] The second objective of this invention is to provide a method for preparing an antistatic visible pipe material, comprising the following steps:

[0027] (1) Weigh each component according to the weight parts, and dry the transparent polyamide matrix at 80-100℃ for 4-8 hours to make the moisture content ≤0.1wt%;

[0028] (2) The dried transparent polyamide matrix, polyether ester amide permanent antistatic agent, polyether block amide auxiliary antistatic agent, quaternary ammonium salt surfactant, maleic anhydride grafted polyolefin elastomer compatibilizer, ultra-high molecular weight polysiloxane lubricant and hindered phenol / phosphite composite antioxidant are added to a high-speed mixer and mixed for 10-20 minutes to obtain a premix.

[0029] (3) The premixed material is added to a twin-screw extruder for melt blending and extrusion granulation to obtain antistatic visible pipe material granules; wherein the length-to-diameter ratio of the screw of the twin-screw extruder is 36:1 to 44:1, the processing temperature is 200 to 260℃, and the screw speed is 200 to 400 rpm;

[0030] (4) After drying the antistatic visible pipe material granules at 80-100℃ for 3-6 hours, they are extruded and molded by a single screw extruder or a pipe extruder to obtain the antistatic visible pipe material; wherein the extrusion molding temperature is 200-250℃ and the extrusion pressure is 8-15MPa.

[0031] Preferably, in step (3), the processing temperature from the feeding section to the die head is 200℃, 220℃, 240℃, 250℃, 250℃, 240℃, and the screw speed is 300rpm.

[0032] Preferably, the pipe material has a light transmittance of ≥85% and a surface resistivity of 10. 6 ~10 10 Ω / sq, coefficient of friction ≤0.25, and meets GB 4806 food contact material safety standard.

[0033] The core innovation of this invention lies in the construction of a "ternary synergistic antistatic system." Through the synergistic compounding of a polyether ester amide permanent antistatic agent, a polyether block amide auxiliary antistatic agent, and a quaternary ammonium salt surfactant, a multi-layered, multi-scale conductive network is formed within a transparent polyamide matrix, achieving long-lasting and stable electrostatic dissipation. The specific technical principle is as follows:

[0034] Polyether ester amide permanent antistatic agents provide a bulk permanent antistatic network, polyether block amide auxiliary antistatic agents expand conductive channels and improve toughness, and quaternary ammonium salt surfactants provide immediate surface antistatic effects. The synergistic effect of these three agents enables the material to achieve a surface resistivity of 10-1 even with low total addition amounts (11.5–28 parts). 6 ~10 10 It achieves a stable antistatic effect with an Ω / sq ratio while maintaining a light transmittance of ≥85%. Neither single-component nor two-component blends can simultaneously meet the comprehensive requirements of antistatic performance, transparency, and mechanical properties.

[0035] As can be seen from the above technical solution, compared with the prior art, the beneficial effects achieved by the present invention include at least the following:

[0036] (1) High light transmittance and visibility: The pipeline material prepared with transparent polyamide with a light transmittance of ≥88% as the matrix and a transparent organic antistatic system has a light transmittance of ≥85%, which can realize visual monitoring of the entire process of filter rod conveying and timely detection of abnormalities such as material blockage and filter rod damage.

[0037] (2) Long-lasting antistatic effect: The ternary synergistic antistatic system simultaneously constructs a conductive network inside and on the surface of the material, and the surface resistivity is stabilized at 10. 6 ~10 10 Ω / sq, electrostatic decay time <0.5s, effectively suppressing electrostatic accumulation and reducing dust adsorption and filter rod adhesion.

[0038] (3) Low friction and anti-sticking: Ultra-high molecular weight polysiloxane lubricant forms a low surface energy lubricating layer on the material surface with a friction coefficient ≤0.25, which effectively reduces the conveying resistance of the filter rod, improves the conveying efficiency, and reduces the wear on the surface of the filter rod.

[0039] (4) Food-grade and non-toxic: All components comply with GB 4806 food contact material safety standards, with no harmful substances migrating, ensuring the quality and safety of filter rod products.

[0040] (5) One-time extrusion molding: No external coating is required. Pipe materials can be prepared by a two-step process of twin-screw melt blending and single-screw extrusion molding. The process is simple and suitable for large-scale production.

[0041] (6) High degree of automation: The long-lasting antistatic transparent and visible pipe of the present invention, which is integrally extruded and molded, serves as a hardware carrier and can integrate multiple sensors such as infrared sensors and vision sensors. It takes into account both detection speed and recognition accuracy, and can simultaneously monitor three types of faults: pipe blockage, filter rod damage, and pipe body failure. It is suitable for continuous and intelligent production lines in cigarette factories. Detailed Implementation

[0042] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0043] All raw materials used in this invention are commercially available industrial-grade or food-grade products, with specific specifications as follows:

[0044] Transparent polyamide PA12, number average molecular weight 30,000, light transmittance 90%, water content ≤0.08%, Evonik / Arkema;

[0045] Transparent copolyamide PA (MACM12), number average molecular weight 25,000, light transmittance 92%, Mitsubishi Gas;

[0046] Polyether ester amide permanent antistatic agent, brand name PES-AM, number average molecular weight 12000, PEG content 50wt%, Clariant;

[0047] Polyether block amide PEBAX, grade PEBAX 2533, Shore hardness 65D, melting point 152℃, Arkema;

[0048] Dioctadecyl dimethyl ammonium chloride, purity ≥95%, Sinopharm Group;

[0049] POE-g-MAH, MAH grafting rate 1.2wt%, MI=5g / 10min, Dow Chemical;

[0050] Ultra-high molecular weight polysiloxane, molecular weight 2 million, viscosity 50,000 cSt, Dow Corning;

[0051] Antioxidant 1076, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, BASF;

[0052] Antioxidant 168, tris(2,4-di-tert-butylphenyl) phosphite, BASF.

[0053] Example 1

[0054] An antistatic visible conduit material for conveying cigarette filter rods, comprising the following components by weight:

[0055] Transparent polyamide PA12: 70 parts

[0056] Polyether ester amide permanent antistatic agent (PES-AM): 12 parts

[0057] Polyether block amide PEBAX 2533: 5 parts

[0058] Dioctadecyl dimethyl ammonium chloride: 1 part

[0059] POE-g-MAH compatibilizer: 3 parts

[0060] Ultra-high molecular weight polysiloxane lubricant: 0.8 parts

[0061] Antioxidant 1076: 0.4 parts

[0062] Antioxidant 168: 0.3 parts

[0063] Preparation method:

[0064] (1) Dry transparent polyamide PA12 at 90℃ for 6 hours to make the moisture content ≤0.1wt%;

[0065] (2) The dried PA12, polyether ester amide permanent antistatic agent, PEBAX 2533, dioctadecyl dimethyl ammonium chloride, POE-g-MAH, ultra-high molecular weight polysiloxane, antioxidant 1076 and antioxidant 168 are added to a high-speed mixer and mixed for 15 min to obtain a premix.

[0066] (3) Add the premixed material to a twin-screw extruder for melt blending and extrusion granulation; wherein the twin-screw extruder has a screw length-to-diameter ratio of 40:1, the processing temperature from the feeding section to the die head is 200℃, 220℃, 240℃, 250℃, 250℃, 240℃, and the screw speed is 300rpm;

[0067] (4) After drying the granules obtained in step (3) at 90°C for 4 hours, they are extruded through a pipe extruder to obtain an antistatic visible pipe material; wherein the extrusion molding temperature is 220°C and the extrusion pressure is 10MPa.

[0068] Example 2

[0069] An antistatic visible conduit material for conveying cigarette filter rods, comprising the following components by weight:

[0070] Transparent polyamide PA12: 75 parts

[0071] Polyether ester amide permanent antistatic agent (PES-AM): 10 parts

[0072] Polyether block amide PEBAX 2533: 4 parts

[0073] Methylbis(2-hydroxyethyl)cocoyl ammonium chloride: 0.8 parts

[0074] POE-g-MAH compatibilizer: 3 parts

[0075] Ultra-high molecular weight polysiloxane lubricant: 0.5 parts

[0076] Antioxidant 1076: 0.35 parts

[0077] Antioxidant 168: 0.25 parts

[0078] The preparation method is the same as in Example 1.

[0079] Example 3

[0080] An antistatic visible conduit material for conveying cigarette filter rods, comprising the following components by weight:

[0081] Transparent polyamide PA12: 65 parts

[0082] Polyether ester amide permanent antistatic agent (PES-AM): 15 parts

[0083] Polyether block amide PEBAX 2533: 6 parts

[0084] Dioctadecyl dimethyl ammonium chloride: 1.2 parts

[0085] POE-g-MAH compatibilizer: 4 parts

[0086] Ultra-high molecular weight polysiloxane lubricant: 1.0 part

[0087] Antioxidant 1076: 0.4 parts

[0088] Antioxidant 168: 0.3 parts

[0089] The preparation method is the same as in Example 1.

[0090] Example 4

[0091] An antistatic visible conduit material for conveying cigarette filter rods, comprising the following components by weight:

[0092] Transparent polyamide PA12: 62 parts

[0093] Polyether ester amide permanent antistatic agent (PES-AM): 18 parts

[0094] Polyether block amide PEBAX 2533: 7 parts

[0095] Dioctadecyl dimethyl ammonium chloride: 1.5 parts

[0096] POE-g-MAH compatibilizer: 4.5 parts

[0097] Ultra-high molecular weight polysiloxane lubricant: 1.2 parts

[0098] Antioxidant 1076: 0.5 parts

[0099] Antioxidant 168: 0.3 parts

[0100] The preparation method is the same as in Example 1.

[0101] Example 5

[0102] An antistatic visible conduit material for conveying cigarette filter rods, comprising the following components by weight:

[0103] Transparent copolyamide PA (MACM12): 68 parts

[0104] Polyether ester amide permanent antistatic agent (PES-AM): 14 parts

[0105] Polyether block amide PEBAX 2533: 5 parts

[0106] Dioctadecyl dimethyl ammonium chloride: 1 part

[0107] POE-g-MAH compatibilizer: 3.5 parts

[0108] Ultra-high molecular weight polysiloxane lubricant: 0.8 parts

[0109] Antioxidant 1076: 0.4 parts

[0110] Antioxidant 168: 0.3 parts

[0111] The preparation method is the same as in Example 1, except that the drying temperature is 80°C.

[0112] Example 6

[0113] An antistatic visible conduit material for conveying cigarette filter rods, comprising the following components by weight:

[0114] Transparent polyamide PA12 / PA(MACM12) blend (mass ratio 7:3): 70 parts

[0115] Polyether ester amide permanent antistatic agent (PES-AM): 12 parts

[0116] Polyether block amide PEBAX 2533: 5 parts

[0117] Dioctadecyl dimethyl ammonium chloride: 1 part

[0118] EPDM-g-MAH compatibilizer: 3 parts

[0119] Ultra-high molecular weight polysiloxane lubricant: 0.8 parts

[0120] Antioxidant 1076: 0.4 parts

[0121] Antioxidant 168: 0.3 parts

[0122] The preparation method is the same as in Example 1.

[0123] Comparative Example 1

[0124] Free of antistatic agents: By weight, it includes the following components: transparent polyamide PA12 94.7 parts, POE-g-MAH compatibilizer 3 parts, ultra-high molecular weight polysiloxane lubricant 0.8 parts, antioxidant 1076 0.4 parts, antioxidant 168 0.3 parts.

[0125] The preparation method is the same as in Example 1.

[0126] Comparative Example 2

[0127] Contains only a single antistatic agent: by weight, it includes the following components: 70 parts transparent polyamide PA12, 20 parts polyether ester amide permanent antistatic agent (PES-AM), 3 parts POE-g-MAH compatibilizer, 0.8 parts ultra-high molecular weight polysiloxane lubricant, 0.4 parts antioxidant 1076, and 0.3 parts antioxidant 168.

[0128] The preparation method is the same as in Example 1.

[0129] Comparative Example 3

[0130] Contains only a single antistatic agent: by weight, it includes the following components: 70 parts transparent polyamide PA12, 20 parts polyether block amide PEBAX 2533, 3 parts POE-g-MAH compatibilizer, 0.8 parts ultra-high molecular weight polysiloxane lubricant, 0.4 parts antioxidant 1076, and 0.3 parts antioxidant 168.

[0131] The preparation method is the same as in Example 1.

[0132] Comparative Example 4

[0133] Compatibilizer-free: By weight, it includes the following components: 73 parts transparent polyamide PA12, 12 parts polyether ester amide permanent antistatic agent (PES-AM), 5 parts polyether block amide PEBAX 2533, 1 part dioctadecyl dimethyl ammonium chloride, 0.8 parts ultra-high molecular weight polysiloxane lubricant, 0.4 parts antioxidant 1076, and 0.3 parts antioxidant 168.

[0134] The preparation method is the same as in Example 1.

[0135] Comparative Example 5

[0136] Lubricant-free: By weight, it includes the following components: 70.8 parts transparent polyamide PA12, 12 parts polyether ester amide permanent antistatic agent (PES-AM), 5 parts polyether block amide PEBAX 2533, 1 part dioctadecyl dimethyl ammonium chloride, 3 parts POE-g-MAH compatibilizer, 0.4 parts antioxidant 1076, and 0.3 parts antioxidant 168.

[0137] The preparation method is the same as in Example 1.

[0138] Comparative Example 6

[0139] Excessive antistatic agent added: by weight, it includes the following components: 55 parts transparent polyamide PA12, 22 parts polyether ester amide permanent antistatic agent (PES-AM), 10 parts polyether block amide PEBAX 2533, 2 parts dioctadecyl dimethyl ammonium chloride, 5 parts POE-g-MAH compatibilizer, 1.5 parts ultra-high molecular weight polysiloxane lubricant, 0.5 parts antioxidant 1076, and 0.3 parts antioxidant 168.

[0140] The preparation method is the same as in Example 1.

[0141] The performance tests for Examples 1-6 and Comparative Examples 1-6 are as follows:

[0142] (1) Surface resistivity: According to GB / T 1410-2006 standard, a high resistance meter was used for testing, with a test voltage of 500V and a test time of 60s.

[0143] (2) Transmittance: According to GB / T 2410-2008 standard, it was tested using a UV-Vis spectrophotometer with a wavelength of 550nm and a sample thickness of 3mm.

[0144] (3) Coefficient of friction: According to GB / T 10006-2021 standard, the coefficient of friction was tested using a coefficient of friction tester with a load of 200g and a sliding speed of 100mm / min.

[0145] (4) Haze: Tested according to GB / T 2410-2008 standard.

[0146] (5) Tensile strength and elongation at break: Tested using a universal testing machine according to GB / T 1040.2-2006 standard, with a tensile speed of 50 mm / min.

[0147] (6) Notched impact strength of simply supported beam: tested according to GB / T 1043.1-2008 standard.

[0148] (7) Food safety: The total migration was tested according to GB 4806.6-2016 standard (4% acetic acid, 70℃, 2h).

[0149] The test results are shown in Table 1.

[0150] Table 1

[0151]

[0152] Comparative Example 1 and Comparative Example 1: The surface resistivity of Comparative Example 1 is >10.13 Ω / sq, completely lacking antistatic capability; Example 1, by adding a ternary synergistic antistatic system, reduced the surface resistivity to 3.2×10 Ω / sq. 8 The Ω / sq ratio was reduced by 5 orders of magnitude, demonstrating the effectiveness of the ternary antistatic system.

[0153] Comparative Example 1 and Comparative Example 2: Comparative Example 2 used only polyether ester amide permanent antistatic agent, with an addition amount of 20 parts (higher than the total addition amount of 18 parts in the ternary system of Example 1), but the surface resistivity was 6.8 × 10⁻⁶. 10 The Ω / sq ratio is two orders of magnitude higher than that of Example 1. This demonstrates that in the ternary synergistic system, the addition of polyether block amide-assisted antistatic agent and quaternary ammonium salt surfactant significantly expands the connectivity of the conductive network, achieving a synergistic effect of 1+1+1>3.

[0154] Comparative Example 1 and Comparative Example 3: Comparative Example 3 used only polyether block amide PEBAX, with an addition amount of 20 parts, but its surface resistivity was 9.2 × 10⁻⁶. 11 The Ω / sq is three orders of magnitude higher than that of Example 1. This demonstrates that the antistatic effect of a single PEBAX is far inferior to that of the ternary synergistic system.

[0155] Comparative Example 1 and Comparative Example 4: Comparative Example 4 does not contain POE-g-MAH compatibilizer, and its surface resistivity is as high as 2.5 × 10⁻⁶. 12 The Ω / sq is four orders of magnitude higher than that of Example 1; however, the tensile strength is only 38.5 MPa (52.3 MPa in Example 1), the elongation at break is only 95% (185% in Example 1), and the notched impact strength is only 6.2 kJ / m. 2 (Example 1: 12.6 kJ / m) 2 This demonstrates that the compatibilizer plays a crucial interfacial compatibilizing role between the antistatic component and the PA matrix: (1) improving the dispersibility of the antistatic component and preventing agglomeration; (2) enhancing interfacial bonding and improving mechanical properties; and (3) promoting the uniform construction of the conductive network.

[0156] Comparing Example 1 with Comparative Example 5: Comparative Example 5, which does not contain ultra-high molecular weight polysiloxane lubricant, has a coefficient of friction of 0.35 (compared to 0.18 in Example 1), nearly twice as high. This demonstrates that ultra-high molecular weight polysiloxane forms a low surface energy lubricating layer on the material surface, significantly reducing the coefficient of friction, which is crucial for the high-speed delivery of filter rods.

[0157] Furthermore, comparing the formulation designs of Examples 1-4: the total addition amounts of the ternary antistatic system in Examples 1-4 were 18 parts, 14.8 parts, 22.2 parts, and 26.5 parts, respectively, corresponding to surface resistivities of 3.2 × 10⁻⁶. 8 Ω / sq, 8.5×10 9Ω / sq, 5.6×10 7 Ω / sq, 2.1×10 7 Ω / sq. It can be seen that:

[0158] When the total amount of antistatic agent increased from 14.8 parts to 26.5 parts, the surface resistivity increased from 10... 9 Reduced to 10 7 Ω / sq, with continuously improved antistatic properties;

[0159] However, when the total amount of antistatic agent reached 26.5 parts (Comparative Example 6, total amount 34 parts), the light transmittance decreased from 87.2% to 78.5%, the haze increased from 5.8% to 15.2%, the tensile strength decreased from 52.3 MPa to 32.5 MPa, and the total migration decreased from 1.8 mg / dm³. 2 Increased to 4.5 mg / dm 2 .

[0160] This proves that the present invention controls the total amount of the ternary antistatic system within the range of 11.5 to 28 parts (preferably 15 to 23 parts), which is the optimal range obtained through experimental screening, and can achieve the best balance between antistatic performance, transparency, mechanical properties and food safety.

[0161] Comparative Example 1 (polyether ester amide permanent antistatic agent: polyether block amide auxiliary antistatic agent: quaternary ammonium salt surfactant = 12:5:1) with Comparative Example 2 (polyether ester amide permanent antistatic agent component only, 20 parts) and Comparative Example 3 (polyether block amide auxiliary antistatic agent component only, 20 parts):

[0162] Example 1: With a total antistatic agent content of 18 parts, the surface resistivity was 3.2 × 10⁻⁶. 8 Ω / sq;

[0163] Comparative Example 2, with a total antistatic agent content of 20 parts, had a surface resistivity of 6.8 × 10⁻⁶. 10 Ω / sq;

[0164] Comparative Example 3, with a total antistatic agent content of 20 parts, had a surface resistivity of 9.2 × 10⁻⁶. 11 Ω / sq.

[0165] In other words, Example 1 achieved better antistatic effects (2-3 orders of magnitude lower) with a smaller total amount of antistatic agent, while also exhibiting higher light transmittance and superior mechanical properties. This fully demonstrates that the proportions of the components in the ternary synergistic antistatic system were not chosen conventionally, but rather were the optimal proportions obtained through experimental screening.

[0166] Comparing Examples 1, 5, and 6: all three polyamide matrices achieved a transmittance of ≥85%, but PA(MACM12) exhibited the highest transmittance (89.5%), and the PA12 / PA(MACM12) blend demonstrated the best overall performance. This proves that the selection of a transparent polyamide matrix requires comprehensive consideration of transmittance, processability, and compatibility with the antistatic system.

[0167] In summary, this invention, through the meticulous design of a ternary synergistic antistatic system, constructs a multi-layered, multi-scale conductive network within a transparent polyamide matrix, achieving a surface resistivity of 10 for the antistatic visible conduit material. 6 ~10 10 Ω / sq, transmittance ≥85%, coefficient of friction ≤0.25, total migration ≤3mg / dm 2 With its durable antistatic properties, it is particularly suitable for pneumatic conveying systems for cigarette filter rods. It can replace traditional stainless steel pipes, enabling full-process visual monitoring, stable static dissipation, and low-friction, high-efficiency conveying, and has significant industrial application value.

[0168] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0169] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An antistatic visible conduit material for conveying cigarette filter rods, characterized in that, By weight, it includes the following components: 60-80 parts of transparent polyamide matrix 8-18 parts of polyether ester amide permanent antistatic agent 3-8 parts of polyether block amide auxiliary antistatic agent 0.5 to 2 parts of quaternary ammonium salt surfactant 2-5 parts of maleic anhydride-grafted polyolefin elastomer compatibilizer 0.3–1.5 parts of ultra-high molecular weight polysiloxane lubricant 0.2–0.8 parts of hindered phenol / phosphite composite antioxidant; in, The transparent polyamide matrix is ​​one or a combination of two of semi-aromatic transparent polyamide or long-chain transparent polyamide, and has a light transmittance of ≥88% under test conditions of wavelength 550nm and material thickness of 3mm; The number average molecular weight of the polyether ester amide permanent antistatic agent is 8000-20000; The polyether block amide auxiliary antistatic agent has a number average molecular weight of 5000 to 15000.

2. The antistatic visible pipe material according to claim 1, characterized in that, The transparent polyamide matrix is ​​selected from at least one of PA12, PA612, PA1012, transparent copolyamide PA (MACM12), and transparent copolyamide PA (PACM12), with a number average molecular weight of 15,000 to 50,000 and a water content of ≤0.1wt%.

3. The antistatic visible pipe material according to claim 1, characterized in that, The polyether ester amide permanent antistatic agent is a polyether ester amide block copolymer, wherein the content of polyether soft segment is 40-60 wt% and the content of polyamide hard segment is 40-60 wt%; the polyether soft segment is one or a combination of two of polyethylene glycol or polytetrahydrofuran, with a number average molecular weight of 1000-4000.

4. The antistatic visible pipe material according to claim 1, characterized in that, The polyether block amide auxiliary antistatic agent is a PEBAX type polyether block amide with a Shore hardness of 60A to 72D and a melting point of 130 to 170°C.

5. The antistatic visible pipe material according to claim 1, characterized in that, The maleic anhydride-grafted polyolefin elastomer compatibilizer is one of POE-g-MAH or EPDM-g-MAH, and the maleic anhydride grafting rate is 0.5 to 2.0 wt%.

6. The antistatic visible pipe material according to claim 1, characterized in that, The ultra-high molecular weight polysiloxane lubricant has a molecular weight of 500,000 to 5,000,000.

7. The antistatic visible pipe material according to claim 1, characterized in that, The quaternary ammonium salt surfactant is one of bis(octadecyl)dimethylammonium chloride or methylbis(2-hydroxyethyl)cocoylammonium chloride.

8. The antistatic visible pipe material according to claim 1, characterized in that, The hindered phenol / phosphite composite antioxidant is a compound of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl)phosphite, with a mass ratio of 1:1 to 2:

1.

9. A method for preparing an antistatic visible pipe material as described in any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Weigh each component according to the weight parts, and dry the transparent polyamide matrix at 80-100℃ for 4-8 hours to make the moisture content ≤0.1wt%; (2) The dried transparent polyamide matrix, polyether ester amide permanent antistatic agent, polyether block amide auxiliary antistatic agent, quaternary ammonium salt surfactant, maleic anhydride grafted polyolefin elastomer compatibilizer, ultra-high molecular weight polysiloxane lubricant and hindered phenol / phosphite composite antioxidant are added to a high-speed mixer and mixed for 10-20 minutes to obtain a premix. (3) The premixed material is added to a twin-screw extruder for melt blending and extrusion granulation to obtain antistatic visible pipe material granules; wherein the length-to-diameter ratio of the screw of the twin-screw extruder is 36:1 to 44:1, the processing temperature is 200 to 260℃, and the screw speed is 200 to 400 rpm; (4) After drying the antistatic visible pipe material granules at 80-100℃ for 3-6 hours, they are extruded and molded by a single screw extruder or a pipe extruder to obtain the antistatic visible pipe material; wherein the extrusion molding temperature is 200-250℃ and the extrusion pressure is 8-15MPa.

10. The preparation method according to claim 9, characterized in that, In step (3), the processing temperatures from the feeding section to the die head are 200℃, 220℃, 240℃, 250℃, 250℃, and 240℃ respectively, and the screw speed is 300 rpm.

Citation Information

Patent Citations

  • A wear-resistant and antistatic polyamide composite material and its preparation method

    CN106967293B

  • Antistatic high-wear-resistance PA66 composite material and preparation method thereof

    CN122188391A